وحدة قصصية رقمية مقترحة في ضوء آراء معلمات الرياضيات والمعايير العالمية لتنمية مهارات تعليم مفاهيمها لدى الطالبات معلمات المرحلة الابتدائية بالكويت - العنزي، دلال فرحان نافع; العنزي، مريم فرحان نافع; الضفيري، ناجي بدر (جامعة القاهرة - كلية الدراسات العليا للتربية, 2021)
تقدم الدراسة وحدة تدريبية مقترحة لاستخدام القصة الرقمية في توصيل المفاهيم الرياضية وفق معايير الرياضيات العالميةTeachers of Mathematics (NCTM) National Council of والمعايير العالمية للتربية العلمية.National Science Education Standards (NSES). تم تطبيق الدراسة على (٤٠) طالبة معلمة في كلية التربية الأساسية تخصص رياضيات/علوم، حيث تم تدريبهن على كتابة قصة وتنفيذها إلكترونيا، وقد تم عرض مجموعة من القصص المصورة إلكترونيا من إعدادهن بعد انتهاء فترة التدريب، وأظهرت النتائج فاعلية الوحدة المقترحة في تنمية مهارات تعليم مفاهيم الرياضيات لدى عينة الدراسة، كما صممت استبانة لاستطلاع رأي أهل الميدان عن فاعلية استخدام أسلوب القصة الرقمية في تعليم المفاهيم العلمية، وطبقت على عينة من معلمات الرياضيات في المرحلة الابتدائية (١٨٦) في الفصل الدراسي الأول ٢٠١٩- ٢٠٢٠، وقد اتبع المنهج الوصفي، وأظهرت النتائج وجود فروق ذات دلالة إحصائية تبعا لسنوات الخبرة في كل من محاور: الفوائد، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية تبعا لأسلوب التدريس في محور فوائد استخدام القصة الرقمية وأن المعلمات اللواتي يستخدمن أسلوب القصة الرقمية يرتفع تقديرهن لفوائد استخدامها عن المعلمات اللواتي يستخدمن أساليب أخرى.
This study provides a proposed training unit to use the digital story in communicating mathematical concepts in the light of the standards of National Council of Teachers of Mathematics (NCTM) and the National Science Education Standards (NSES). The study was administered to 40 female student teachers at the Faculty of Basic Education majoring in Mathematics/ Science. The participants were trained to write a story to be implemented electronically. Furthermore, a set of stories were presented electronically which were prepared after the end of the training period. The results showed the effectiveness of the proposed unit in developing the skills of teaching the mathematical concepts among the study sample. Furthermore, a questionnaire was designed to survey the opinions of stakeholders concerning the effectiveness of using the digital story in teaching scientific concepts. The study was administered to a sample of mathematics teachers of the elementary stage (186) during the first semester of the academic year 2019-2020 making use of the descriptive method. The results showed that there were statistically significant differences in terms of the yearsof experience in each of the dimensions of the benefits. The results also showed that there were statistically significant differences in terms of the teaching method in the dimension of benefits of using the digital story, as the female teachers who use the digital story method had higher degrees of appreciation of the benefits of using stories than the female teachers who use other methods.
Keywords: إعداد المعلمين -- معلمو الرياضيات -- تدريس الرياضيات -- المفاهيم الرياضية -- القصص الرقمية -- المهارات التدريسية -- معلمو المرحلة الابتدائية -- الكويت